2021
DOI: 10.1128/aem.01403-20
|View full text |Cite|
|
Sign up to set email alerts
|

Phylogenetic and Biogeographic Patterns of Vibrio parahaemolyticus Strains from North America Inferred from Whole-Genome Sequence Data

Abstract: Vibrio parahaemolyticus is the most common cause of seafood-borne illness reported in the United States. Draft genomes of 132 North American clinical and oyster V. parahaemolyticus isolates were sequenced to investigate their phylogenetic and biogeographic relationships. The majority of oyster isolate sequence types (STs) were from a single harvest location; however, four were identified from multiple locations. There was population structure along the Gulf and Atlantic Coasts of North America, with what seeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…These genetic features underlie the non-robust MLST interpretation. Our results supported those of previous studies which showed that WGS analyses could yield enhanced resolution for V. parahaemolyticus classification; nevertheless, conventional MLST is a reliable tool that can generate phylogenetic data for the V. parahaemolyticus genome when WGS is unavailable ( 68 ). The limitation in our study was the uncertain origin of bird fecal samples.…”
Section: Discussionsupporting
confidence: 91%
“…These genetic features underlie the non-robust MLST interpretation. Our results supported those of previous studies which showed that WGS analyses could yield enhanced resolution for V. parahaemolyticus classification; nevertheless, conventional MLST is a reliable tool that can generate phylogenetic data for the V. parahaemolyticus genome when WGS is unavailable ( 68 ). The limitation in our study was the uncertain origin of bird fecal samples.…”
Section: Discussionsupporting
confidence: 91%
“…V. parahaemolyticus, a halophilic, Gram-negative bacterium that inhabits coastal estuarine environments, poses a major threat to human health worldwide V.…”
Section: Resultsmentioning
confidence: 99%
“…parahaemolyticus is the leading cause of seafood-borne infections globally. It can result in mild to acute gastroenteritis, wound infections, ear infections, and even sepsis . Currently, multidrug-resistant V.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations